Attitudes of Primary School Teachers Toward Inclusive Education - Radojlovic, Jasmina; Kilibarda, Tatjana; Radevic, Svetlana; Maricic, Milena; Parezanovic Ilic, Katarina; Djordjic, Milan; Colovic, Sofija; Radmanovic, Branimir; Sekulic, Marija; Djordjevic, Ognjen; Niciforovic, Jovan; Simic Vukomanovic, Ivana; et al. (Frontiers in Psychology, 2022)
Background The aims of our study are related to examining the relevance of teachers' attitudes toward the implementation of inclusive education. In addition, its subject is related to the implications on inclusive education policies, limitations of the existing study along with the recommendations for our future research endeavors. Methods The research is a cross-sectional study type. The sample included 64 primary school teachers in the lower grades of primary school (grades 1–4), selected by using simple random sampling, in three primary schools on the territory of Belgrade, Serbia in 2021 (26, 17, and 21 primary school teachers). The Questionnaire for Teachers, which was used as a research instrument, was taken from the Master's Thesis Studen Rajke, which was part of the project “Education for the Knowledge Society” at the Institute for Educational Research in Belgrade. Dependent variables measured in the study referred to the attitudes of primary school teachers toward inclusive education. Categorical variables are represented as frequencies and the Chi-square test was used to determine if a distribution of observed frequencies differed from the expected frequencies. Results One in three teachers (32.8%) thought that inclusion was useful for children with disabilities (29.7%), of them thought that schools did not have the conditions for inclusive education, whereas one in four teachers (25.0%) believed that inclusion was not good. No statistically significant differences were found in the attitudes of professors, when observed in terms of their gender, age and length of service. Conclusion Investing more resources and time in developing and implementing special education policies can promote successful inclusive education.